Analisis Penggunaan Kecerdasan Buatan ChatGPT dalam Penulisan Karya Publikasi Ilmiah: Manfaat dan Tantangan - Wafi, Wafi Ariqo; Rizal, Edwin; Winoto, Yunus (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study discusses the use of artificial intelligence (AI), specifically ChatGPT, in the process of writing scientific publications. ChatGPT, based on the Generative Pre-trained Transformer (GPT) model, significantly aids the writing process by efficiently generating text. While this technology can enhance productivity, there are risks such as plagiarism, information inaccuracies, and a decline in the originality of academic work. The research employed a qualitative method with a case study approach, involving observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that ChatGPT speeds up the writing process and helps generate ideas, but caution is needed regarding potential biases and ethical concerns. This study recommends verifying information and maintaining the originality of academic work to optimize the use of AI in the academic world.